Activation of Microbiota Sensing – Free Fatty Acid Receptor 2 Signaling Ameliorates Amyloid-β Induced Neurotoxicity by Modulating Proteolysis-Senescence Axis - Razazan, Atefeh; Karunakar, Prashantha; Mishra, Sidharth P.; Sharma, Shailesh; Miller, Brandi; Jain, Shalini; Yadav, Hariom (Frontiers in Aging Neuroscience, 2021)
Emerging evidence indicates that the gut microbiota contributes to the pathology of Alzheimer’s disease (AD) - a debilitating public health problem in older adults. However, strategies to beneficially modulate gut microbiota and its sensing signaling pathways remain largely unknown. Here, we screened, validated, and established the agonists of free fatty acid receptor 2 (FFAR2) signaling, which senses beneficial signals from short chain fatty acids (SCFAs) produced by microbiota in the gut. The abundance of beneficial metabolites, such as SCFAs, is often low in the gut of older adults with AD. We demonstrated that inhibition of FFAR2 signaling increases amyloid-beta (Aβ) stimulated neuronal toxicity. Thus, we screened FFAR2 agonists using an in-silico library of more than 144,000 natural compounds and selected 15 compounds based on binding with FFAR2-agonist active sites. Fenchol (a natural compound commonly present in basil) was recognized as a potent FFAR2 agonist in neuronal cells and demonstrated protective effects against Aβ-stimulated neurodegeneration in an FFAR2-dependent manner. In addition, Fenchol reduced AD-like phenotypes, such as Aβ-accumulation, and impaired learning and memory behaviors in Caenorhabditis (C.) elegans and mice models, by increasing Aβ-clearance via the promotion of proteolysis and reduced senescence in neuronal cells. These results suggest that the inhibition of FFAR2 signaling promotes Aβ-induced neurodegeneration, while the activation of FFAR2 by Fenchol ameliorates these abnormalities by promoting proteolytic Aβ-clearance and reducing cellular senescence. Thus, stimulation of FFAR2 signaling by Fenchol as a natural compound can be a therapeutic approach to ameliorate AD pathology.